THE RETHINKING OF COMMUNICATION IDENTITY OF COPAS USTAZAH IN THE WAG: CASE STUDY IN “GROUP OF MOTHERS WHO LOVE SHARING” - Pambayun, Ellys Lestari; Fahruddin, Ahmad (Harmoni, 2023)
The issue that becomes the focus is the phenomenon of identity formation “like an ustazah” which was built by “ Group of Mothers Who Love Sharing in Bojong” through the habit of copying verses, hadith, religious studies, and tafsir. Their behavior is often without filters, explanations, and text corrections. The research method used is Communication Mediated Computer (CMC) with online interview and online discussion. Research findings report that in the view of identity communication, the formation of identity in the Group of Mothers Who Love Sharing Bojong is built through symbolic activities resulting from the fusion of their characters and thoughts with their social environment. Meanwhile, from a feminine writing perspevtive criticizes that copypas behavior in WAG indicates a sexist and ideological structure: women who do not write in their own language and body are assumed they deny their independence, authenticity, transformation, and strength. In conclusion, women can actually preach on social media freely and actively, and even become active copy-paste agents but still remain tabayun and critical.